Coaches` perceptions on the Spread: A 1 vs 1 goalkeeper technique. International survey on 400 + goalkeeper coaches - Medina, K. G.; Delvaux, F.; Schwartz, C.; Berwart, G.; Barnerat, T.; Croisier, J.-L.; Kaux, J.-F. (International Journal of Sports Science and Coaching, 2025)
In this study, we explore goalkeeper (GK) coaches` knowledge and use of the Spread, a 1v1 goalkeeping technique, and their experiences and perceptions on injury risks related to it. An online questionnaire was distributed internationally between January and March 2023, collecting a total of 411 complete answers (largest sample of GK coaches to date). GK coaches` demographics were used to explore significant differences between answers. Almost all coaches recognized (99%) and used (78%) the technique. Coaches recommended to start training the Spread from a Recreational level and at an age of 11.3 ± 2.8. Contact with another player was the most (67%) perceived type of injury risk; 38% of the coaches recalled at least one player getting injured performing the Spread (Elite level coaches significantly more likely, p < .01); with Contusion (16.3%) and Musculo-skeletal (15.8%) being the most recalled type of injuries. Most coaches perceived no injury risk differences between male and female GK (68.1%), nor between young and adult GK (41.1%). These results show the Spread's popularity among GK coaches while highlighting knowledge gaps in some areas (e.g., technical execution, sources of knowledge). Both researchers and stakeholders can leverage from the results to develop and improve GK-coaching interventions, particularly in the field of injury prevention.